Collusive upward gasoline price movements in medium-sized German cities - Arne Neukirch; Thomas Wein (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2016)
Do we have effective competition between the gasoline's big five oligopolists (Aral, Shell, Esso, Total and Jet) and fringe gasoline stations? Using 2014 Market Transparency price data from 66 cities with populations between 60,000 and 100,000, we analyze which brands lead price increases, the first average price mark-up in the evening, and the trend on price increases until midnight. Furthermore, we measure the response time it takes for competitors to react to these price increases, and how much prices change from the beginning to the end of a day. By watching local activities of the big brands, it is possible to measure how smaller businesses, such as Jet or independent retailers, react to Aral's and Shell's price changes. Multivariate estimations allows to control for gasoline type (regular or diesel), school holidays, weekends, weekdays, location -such as East or West Germany-, wholesale and starting prices. Descriptive results show the typical patterns. Aral (or Shell) will start a price increase round, and then Shell (or Aral) will more or less immediately follow. Total, Esso and Non-Oligopolists react within one or two hours. Jet behaves more as an "outsider" with later reaction times and lower price mark-ups. Multivariate estimation indicates that the single cause "price change by competitors" is less important and nearly irrelevant for Jet.
Keywords: L13; L41; L81; 330; market power; collusive behavior; gasoline market